2015
DOI: 10.1002/dev.21370
|View full text |Cite|
|
Sign up to set email alerts
|

Individual variation in fathers’ testosterone reactivity to infant distress predicts parenting behaviors with their 1‐year‐old infants

Abstract: Positive father involvement is associated with positive child outcomes. There is great variation in fathers’ involvement and fathering behaviors, and men’s testosterone (T) has been proposed as a potential biological contributor to paternal involvement. Previous studies investigating testosterone changes in response to father-infant interactions or exposure to infant cues are unclear as to whether individual variation in T is predictive of fathering behavior. We show that individual variation in fathers’ T rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
44
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 59 publications
(89 reference statements)
4
44
0
Order By: Relevance
“…For instance, in one laboratory study, men reported greater concern in response to infant cries to the extent that they showed larger reductions in testosterone after listening to those cries; however, as in the current study, men's initial baseline testosterone levels were unrelated to their level of concern (Storey et al, ). Kuo and colleagues () similarly found that fathers who showed larger testosterone declines while interacting with their infant during a stressful laboratory task were more positively engaged with their infants in a subsequent teaching task; again, initial (pre‐task) testosterone levels were unrelated to fathers’ behavior in the teaching task. Short‐term changes in hormones as a function of a laboratory task likely reflect different processes than those that occur over longer periods of time during life transitions such as pregnancy; however, these findings highlight the importance of measuring not only baseline or initial hormone levels but also the extent to which hormones change over time, in both the short‐ and long‐term, as a function of life experiences and contextual influences.…”
Section: Discussionmentioning
confidence: 98%
“…For instance, in one laboratory study, men reported greater concern in response to infant cries to the extent that they showed larger reductions in testosterone after listening to those cries; however, as in the current study, men's initial baseline testosterone levels were unrelated to their level of concern (Storey et al, ). Kuo and colleagues () similarly found that fathers who showed larger testosterone declines while interacting with their infant during a stressful laboratory task were more positively engaged with their infants in a subsequent teaching task; again, initial (pre‐task) testosterone levels were unrelated to fathers’ behavior in the teaching task. Short‐term changes in hormones as a function of a laboratory task likely reflect different processes than those that occur over longer periods of time during life transitions such as pregnancy; however, these findings highlight the importance of measuring not only baseline or initial hormone levels but also the extent to which hormones change over time, in both the short‐ and long‐term, as a function of life experiences and contextual influences.…”
Section: Discussionmentioning
confidence: 98%
“…The average age of men's youngest children in 2014 was 3.7 years. Because of rapid developmental changes during the toddler years, children of this age are more independent than they are at 1.9 years (the mean youngest child age in 2009), but 3‐4‐year‐old children still require extensive care and patience, both of which may be facilitated by lower T (eg, Crnic & Booth, ; Gettler et al, ; Kuo et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, when men hear infant cries while engaging in nurturant behavior, their testosterone levels decline (Kuo et al 2015, van Anders et al 2014). One interpretation of these results is that when men hear infant cries, but are unable to respond to them, cries are perceived as evidence of a threat to the infant that necessitates an aggressive, protective response (van Anders et al 2011).…”
Section: Testosterone and Trade-offs Between Mating Effort And Paternmentioning
confidence: 99%
“…One interpretation of these results is that when men hear infant cries, but are unable to respond to them, cries are perceived as evidence of a threat to the infant that necessitates an aggressive, protective response (van Anders et al 2011). Alternatively, testosterone increases in this context could result from men perceiving infant cries as a kind of social provocation (Kuo et al 2015). …”
Section: Testosterone and Trade-offs Between Mating Effort And Paternmentioning
confidence: 99%